Antecedent of Work Life Balance and Employee Commitment in Ekiti State University, Nigeria - Awolaja, Ayodeji M; Bola, Adekola (Advances in Social Sciences Research Journal, 2023)
The study examined the effects of work-life balance on employee commitment in Ekiti State University. The total population under consideration was eight hundred and two academic staff of Ekiti State University, Ado Ekiti, gotten from the Estab. Academic as at November, 2022. The sample size for this study was three hundred and sixty-seven respondents using convenient technique among the academic staff of Ekiti State University, Ado Ekiti using Taro Yamane (1967) model. The method of data analysis used was simple regression analysis to achieve the stated objectives. The result revealed that there is significant effect of flexible work arrangements, Human Resource family support services and Human Resource financial incentives on employee commitment among employees of Ekiti State University, Ado Ekiti.